Recent Advancement in Boron-Based Efficient and Pure Blue Thermally Activated Delayed Fluorescence Materials for Organic Light-Emitting Diodes - Lee, Hyuna; Karthik, Durai; Lampande, Raju; Ryu, Jae Hong; Kwon, Jang Hyuk (Frontiers in Chemistry, 2020)
In the last few years, electron deficient materials have been actively researched for application in organic light-emitting diode (OLED) as dopant and electron transporting materials. The boron containing materials are interesting as they give good emissive properties in solid state with electron accepting character. Recently, many boron containing materials are used as emissive materials for thermally activated delayed fluorescence (TADF) OLED applications. In this review, boron acceptor-based push-pull small molecules used for application in blue TADF OLEDs are reviewed, covering their different types of acceptor, molecular design, structure-property relation, material properties and device properties. Also, the importance of boron acceptors to address the key issue of blue TADF OLEDs is discussed.